Strengthening Teacher Education Program: Keys to Develop through Teacher Assessment - Tecnam Yoon (Journal of Education and Learning (EduLearn), 2014)
Teacher performance assessment is a part of a global trend based on teacher education program. The purpose of this paper is to investigate the American Teacher Performance Assessment (TPA) program, to identify some of the features in creating a system for pre-service teachers in developing countries, and to suggest an ideal TPA model for strengthening the teacher education program.